DINAMIKA PSIKOLOGIS DAN UPAYA MEMBANGUN KEHARMONISAN RUMAH TANGGA DALAM HUBUNGAN LONG DISTANCE RELATIONSIP (LDR) STUDI PADA TKI DI METRO SELATAN - Damayanti, Wiwik; Khotamin, Nur Alfi; Mujtahid, Muhammad; Signori, Damar Hanif (Institut Agama Islam Ngawi, 2025)
This study examines the psychological dynamics experienced by Indonesian Migrant Workers (TKI) who are in long-distance relationships (LDR) and their efforts to maintain marital harmony. The LDR phenomenon among TKI arises from overseas job placements, which separate couples for extended periods. The aim of this study is to understand the psychological challenges faced by TKI couples and the efforts they make to sustain a harmonious relationship despite the distance. This research uses a qualitative approach with a case study design, involving 6-8 TKI couples in Rejomulyo Village, South Metro, using purposive sampling. Data collection was conducted through in-depth interviews, observations, and documentation, while data analysis was carried out thematically. The results indicate that the psychological dynamics faced by TKI couples include loneliness, anxiety, and emotional stress due to limited physical interaction. However, they strive to maintain marital harmony through effective communication, building trust, and emotional support from family and psychological counseling. Factors influencing marital harmony include regular communication, trust levels, emotional support, and financial planning. This study contributes to understanding the psychological challenges faced by TKI couples in LDR and their efforts to maintain marital harmony despite the distance.